PERFORMING AN ANALYSIS OF ARRAY WAVEGUIDE (AWG) MULTIPLEXER BASED ON AN OPTICAL NETWORK - Hussein Ahmed Ali (Tikrit Journal of Pure Science, 2023)
Rapid advances in optical technology have created potential solutions for enabling high capacity networks. The main problem in optical communication in the Ministry of Communication at the  Republic of  Iraq is dedicating a small bandwidth for each user. Most of the previous works have focused on modifying the characteristics of Array Waveguide Multiplexer (AWG) in the designing level. However, designing of optical communication is expensive which makes these efforts unpractically. Therefore, to develop multi-target communication over the current infrastructure, this paper investigates the performance of the AWG at the components level. In the beginning, an analysis is performed of an AWG at data rates of (8×40Gb/s, over 242.5km fiber optic link) with minimum system impairments. The presence of (Passive/Active) components is taken into considerations. The evaluation is performed using Optisystem software simulation package. By adopting (4.0402dBm) total input signal power, the simulation has achieved (0.3545dBm) total output signal power, (-3.6856dbm) total gain, (1.4248dBm) total output noise, and the average power is (-6.4255dBm). Furthermore, the transmission rates are successfully transmitted delivered in a low-cost infrastructure. Moreover, with the presence of multiple users on a single link, the transmission is performed with a high rapidity in addition to a minimum error. Consequently, the simulations can be applied to the existing fiber communication networks with ultimate reduction of the cost and operational expenditure for the overall network system.